Integrating Local Culture into Creativity Development: A Case Study of the Geti Asem Batik Program in Indonesian Primary Education - Darmaji Darmaji; Triyanto Triyanto; Chumdari Chumdari (STAI Hubbulwathan Duri, 2025)
Local culture holds significant potential to enhance students' creativity, identity, and innovation. However, it remains underutilized in primary education. This study explores the implementation of the Geti Asem (Gerakan Membatik Akhir Semester) program as a means to integrate cultural values into learning and foster creativity among elementary students. This qualitative case study was conducted at SDN 3 Pule, Selogiri District, Wonogiri Regency. Data were collected through observations, interviews, and document analysis involving the principal, two teachers, and 14 fifth-grade students. The data were analyzed using the Miles and Huberman interactive model, employing triangulation techniques for validation. The Geti Asem program is implemented through a participatory approach that engages students directly in the batik-making process. This approach cultivates critical thinking, self-expression, and originality. Teachers serve as facilitators, offering technical guidance while fostering a creative and supportive learning environment. The program is supported by strong moral encouragement from parents, educators, school leaders, and the local community. However, it faces challenges such as limited facilities and tools, which hinder optimal time management and student access during practice. This study demonstrates that local culture-based learning, exemplified by the Geti Asem program, can significantly enrich creativity and character education in primary students. It supports the effective implementation of the Pancasila Student Profile (P5) through a contextual and participatory model, contributing to the broader discourse on cultural pedagogy in Indonesian education.